THE INFLUENCE OF OWNERSHIP STRUCTURE ON FIRM PERFORMANCE AS MEASURED BY TOBIN'S Q - Sitti Mukarromah; Ibnu Suryo; Rochmi Widayanti; Tarisa Firda Saniyyah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This research explores how ownership structure affects corporate performance, as indicated by stock prices using Tobin’s Q. The study focuses on companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The ownership structure is assessed through three dimensions: managerial ownership, public ownership, and the presence of independent commissioners, to determine their individual and combined effects on firm performance. A purposive sampling method was employed, yielding a sample of 33 companies. Data analysis was carried out using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach, utilizing the SmartPLS version 4.10.9 software. Managerial ownership has a significant positive impact on firm performance, while neither public ownership nor independent commissioners show notable influence. However, when considered together, all three variables collectively have a positive impact on firm performance, as measured by Tobin’s Q. Keywords: Ownership structure, firm performance, stock price, Tobin’s Q, SEM-PLS.